US climate policy: A critical assessment of intensity standards - Christoph Böhringer; Xaquín Garcia-Muros; Mikel Gonzalez-Equino; Luis Rey (University of Oldenburg, Department of Economics, 2015)
Intensity standards have gained substantial momentum as a regulatory instrument in US climate policy. Based on numerical simulations with a large-scale computable general equilibrium model we show that intensity standards may rather increase than decrease counterproductive carbon leakage. Moreover, standards can lead to considerable welfare losses compared to emission pricing via carbon taxation or an emissions trading system. The tradability of standards across industries is a mechanism that can reduce these negative effects.
Keywords: D21; H23; D58; 330; unilateral climate policy; carbon leakage; intensity standards; computable general equilibrium